A STIGMASTEROL GLYCOSIDE FROM THE ROOT WOOD OF Melochia Umbellata (Houtt) Stapf var. degrabrata K. - Ahmad Ridhay; Alfian Noor; Nunuk H. Soekamto; Tjodi Harlim; Ian van Altena (Universitas Gadjah Mada, 2012)
A stigmasterol glycoside (stigmast-5,22-dien-3-O-β-D-glucopyranoside) has been isolated from the chloroform fraction of root wood of Melochia umbellata (Houtt) Stapf var. degrabrata K. The compound structure was determined on spectroscopic evidences including IR, 1D and 2D NMR and compared to previous data. The isolate was also active against Aspergillus niger.